Invasive Spartina alterniflora alters sediment organic carbon mineralization dynamics in a coastal wetland of Southeastern China - Jiang, Yongcan; Yang, Dong; Huang, Jiafang; Wen, Yu; Tang, Hong; Xu, Jianming; Lin, Xianbiao; Sun, Dongyao; Gao, Dengzhou (Frontiers in Marine Science, 2024)
Invasive Spartina alterniflora has significant impacts on sediment carbon pool and turnover in the tidal wetlands of estuaries and coasts. Yet, how this exotic S. alterniflora affects sediment organic carbon mineralization dynamics remains poorly understood. In this study, sediment geochemical properties, organic carbon fractions, and mineralization dynamics were examined in a native Cyperus malaccensis habitat and three invasive S. alterniflora habitats (6-, 10-, and 14-year-old) in summer and winter. We found that invasive S. alterniflora generally increased sediment total organic carbon and their labile fraction contents. The organic carbon mineralization rates and cumulative carbon mineralization amounts were significantly influenced by invasive S. alterniflora, and their values increased with this exotic plant invasion chronosequences. The mineralization rates and cumulative mineralization amounts were also characterized by higher values in surface sediment (0 – 10 cm depth) compared to subsurface sediment (10 – 20 cm depth) and by seasonal variations with higher values in summer than in winter. The sediment organic carbon labile fractions, rather than total organic carbon, were the most important factor affecting carbon mineralization dynamics. The cumulative carbon mineralization amounts exhibited an excellent fit to the first-order kinetic equation (R2 ≥ 0.93). The changes in modeled kinetic parameters (potential carbon mineralization amounts (C0) and carbon mineralization rate constant (k)) among these four habitats were similar to carbon mineralization rates, implying invasive S. alterniflora promoted the availabilities of organic compounds for microbial respiration metabolism. Overall, our findings highlighted the importance of S. alterniflora invasion in accelerating organic carbon decomposition and carbon dioxide release potential, although it also increases carbon accumulation.